Use of Limiting Nutrients for Reclamation of Non-responsive Soils in Northern Ghana - Asei, Rechiatu; Abaidoo, Robert Clement; Opoku, Andrews; Adjei-Nsiah, Samuel; Antwi-Agyei, Philip (Frontiers in Soil Science, 2021)
A better understanding of soil fertility factors that constraints positive crop response to fertilizer inputs will facilitate the improvement of soil nutrient managements. In this study, a nutrient omission trial was carried out in a greenhouse condition to identify soil chemical properties limiting in non-responsive soils, and to ascertain their effect on soybean (Glycine max) production. The treatments evaluated were, control (distilled water), complete nutrient solution (all nutrients) and complete solution with the omission of each of N, P, K, Ca, Mg and S, and micronutrients (Fe, Zn, Cu, Mn, B and Mo) arranged in a completely randomised design with three replications. After the greenhouse study, the identified limiting nutrients were tested with or without FertiSoil (commercial compost) in a 3 year field experiment. Results of the soil analyses showed low fertility status of the non-responsive soils. The sufficiency quotient index revealed non-responsive soils in all the sites to be predominantly limiting in P and K. The occurrence of other limiting nutrients were also identified: Pishegu (Zn, B), Serekpere (Mg, S), Daffiama Saapare (Ca, Mg, S) and Naaga (Mg, S, Zn, B). The nutrient inputs positively influenced soybean yield response in all the locations. The application of PKZnB with FertiSoil and FertiSoil alone significantly increased soybean grain yields by 585 and 477 kg ha-1, respectively at Pishegu. Soybean grain yields also increased by 585, 573 and 364 kg ha-1 under the FertiSoil, PKMgS + FertiSoil and PKMgS applications at Serekpere respectively. At Daffiama Saapare, the highest (103%) from the combined application of PKMgSCa and FertiSoil. However, the application of FertiSoil and PKMgSCa singly equally increased soybean grain yield by 77%. Percent soybean grain yield increases of 86, 84 and 74% were observed when PKMgSZnB + FertiSoil, PKMgSZnB and FertiSoil were applied, respectively at Naaga. In absolute terms, 83% of the fields had a positive response to mineral fertilizer and 93% to FertiSoil and mineral fertilizer + FertiSoil applications. Organic amendment and or site-specific fertilizer applications are the best options for alleviating poor or no crop responses to inputs and improve productivity on non-responsive soils.